2004
DOI: 10.1080/0972-060x.2004.10643376
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils composition ofNepeta catariaL. andNepeta crassifoliaBoiss. and Buhse from Iran

Abstract: The essential oils of Nepeta cataria L. and Nepeta crassifolia Boiss. & Buhse (Labiatae) were extracted by hydrodistillation and analyzed using GC and GC/MS. The major components of N. cataria oil were 4a-α,7-α,7a-β-nepetalactone (28.8%), 1,8-cineole (13.5%), 4a-α, 7-β, 7a-α-nepetalactone (11.9%), (E)-caryophyllene (5.7%) and citronellyl acetate (5.2%). The major compounds of N. crassifolia oil were 4a-α,7-β, 7a-α-nepetalactone (81.1%) and 4a-α,7-α,7a-αnepetalactone (5.9%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Different studies have been conducted in other regions on the chemical composition of essential oils from different samples of N. cataria [5,6]. Although the comparison between compounds obtained from this study and other reports show several similarities, there are considerable quantitative and qualitative differences between the samples from different locations in Iran.…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 41%
See 1 more Smart Citation
“…Different studies have been conducted in other regions on the chemical composition of essential oils from different samples of N. cataria [5,6]. Although the comparison between compounds obtained from this study and other reports show several similarities, there are considerable quantitative and qualitative differences between the samples from different locations in Iran.…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 41%
“…The composition varies from region to region, variety, analytical and extraction methods, climatic conditions and vegetation period. The main constituents so far identified, include caryophyllene, caryophyllene oxide, 1,8-cineol, citronellol, geraniol, elemol, nerol, nerolidol, spathulenol, elemene, geranyl acetate, citronellyl acetate and geranial [5,6]. Bacterial infections as well as microorganisms' resistance to antibiotics are well documented in both plants and humans.…”
Section: Introductionmentioning
confidence: 99%
“…It was documented that nepetalactones were the predominant components responsible for the feline attractant properties of many Nepeta species, such as N. persica, N. pogonosperma, N. racemosa, N. cataria, N. sibirica, N. nuda, N. grandifolia, N. clarkei, N. argolica and N. crassifolia. [34][35][36][37][38][39][40][41] For instance, 4aα,7α,7aβ-nepetalactone (28.8%) and 4aα, 7β,7aα-nepetalactone (11.9%) were reported the major components of Nepeta cataria essential oil. [41] Tittel et al [42] reported that the main constituents of N. cataria var.…”
Section: Resultsmentioning
confidence: 99%
“…Morteza-Semnani and Saeedi [41] Nepeta nuda Central Anatolia b-caryophyllene oxide (21.8%), spathulenol (13.8%), allo-aromadendrene (9.0%) b-caryophyllene (5.4%)…”
Section: Resultsmentioning
confidence: 99%
“…Another study of N. crassifolia afforded cirsimaritin and 8‐hydroxycirsimaritin (Jamzad et al , ). The essential oil of the aerial parts of N. crassifolia has been previously studied and showed 4aα,7α,7aα‐nepetalactone, linalyl acetate, piperitone, germacrene D, 4aβ,7α,7aβ‐nepetalactone and β‐caryophyllene as main constituents (Dabiri and Sefidkon, ; Morteza‐Semnani and Saeedi, ).…”
Section: Introductionmentioning
confidence: 99%